Development of Undrained Dynamic-loading Ring-shear Apparatus and Its Application to Landslides in Japan and Indonesia - Sassa, Kyoji (2011)
Landslides are gravitational mass movements of rock, debris or earth. Some move very slowly, thus conforming to the field of statics, but some move rapidly. Study of the initiation and motion of rapid landslides needs to develop "Landslide Dynamics" involving dynamic loading and dynamic generation/dissipation of excess pore-water pressure. New developments in science can be facilitated by new technological advances. This study aimed to develop a new apparatus that can geotechnically simulate the formation of the shear zone and the following long and rapid shear displacement that occurs in high-velocity landslides. An undrained dynamic-loading ring-shear apparatus has been developed for this purpose. A series of different types of apparatus (DPRI-3, 4, 5, 6, 7) have been developed from 1992 to the present.This paper describes the development of this apparatus and its application to the study of earthquake-induced landslides, landslide-triggered debris flow in Japan and rainfall-induced landslide in Banjarnegara Regency, Indonesia. Also, tests of the latest version (DPRI-7) with a transparent shear box for direct observation of the shear zone during a rapid shearing are described. This paper was rewritten from Sassa et at. (2004) including the application to an Indonesian landslide.